Acute, subacute and chronic sequelae of horses accidentally exposed to monensin‐contaminated feed. (24th March 2020) - Gy, Clémentine; Leclere, Mathilde; Bélanger, Marie‐Claude; Allano, Marion; Beauchamp, Guy; Lavoie, Jean‐Pierre
Abstract: Background: Monensin is highly toxic to horses and inadvertent ingestion can result in cardiac injury and death. Objectives: To describe sequelae of monensin ingestion and to determine clinical predictors of outcome. Study design: Observational clinical study. Methods: Physical examination, electrocardiogram and echocardiography were performed on 76 horses accidentally exposed to monensin‐contaminated feed. Four horses were examined within 14 days of exposure (acute period), 29 horses were examined between 15 and 45 days post‐exposure (subacute period) and 70 horses were examined 4‐10 months after exposure (chronic period). Follow‐up information was obtained for 56 horses by telephone interviews approximately 16 months after exposure. Results: Cardiac abnormalities were detected in 4/4, 19/29 and 31/70 horses during the acute, subacute and chronic periods, respectively. Sixteen months post‐exposure, 34 of the 64 horses (53%) for which the outcome was known had returned to their previous use, 13 (20%) were reported to be exercise intolerant, three (5%) were retired and 14 (22%) were dead (two deaths, 12 euthanasia). Thinning of the myocardium observed at any point in time was associated with a negative outcome. Heterogeneity of the myocardium observed in the acute/subacute period was associated with a negative outcome while subjective contractile intraventricular dyssynchrony, cardiac chamber dilation, decreased fractional shortening and multiple premature ventricular complexes observed in the chronic period were associated with a negative outcome. Some horses with significant changes associated with a negative outcome in the chronic phase still returned to their previous work. Main limitations: No control group and only 27 horses were examined more than once. Conclusions: Clinical outcome of horses exposed to sublethal doses of monensin is highly variable. The presence of heterogeneity and thinning of the myocardium shortly after intoxication were associated with a negative outcome.